2020
DOI: 10.1111/jgh.15193
|View full text |Cite
|
Sign up to set email alerts
|

Functional dyspepsia in children: A study of pathophysiological factors

Abstract: Background and Aim Functional dyspepsia (FD) is common in children, and treatment targeted towards the altered pathophysiology can improve outcome. We evaluated FD children for abnormality of gastric accommodation and emptying, psychological stressors (PS), Helicobacter pylori (HP) infection, and post‐infectious FD. Methods Diagnosis of FD was based on ROME III criteria. Clinical evaluation including dyspeptic symptom scoring and assessment for PS was performed. Satiety drink test for gastric accommodation, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although the exact pathogenesis of FD remains unclear, several pathophysiological mechanisms have been proposed to influence the etiology of FD, such as gastroduodenal motor dysfunction, visceral hypersensitivity, low-grade gastroduodenal inflammation, Helicobacter pylori infection, mental stress, and/or abnormal central nervous system processing through the gut-brain axis (Koppen et al, 2017;Walker et al, 2019;Shava et al, 2021). Most pediatricians commonly personalize the patient's medical treatment, including dietary modifications, prokinetics, antacids, antispasmodics, antidepressants, and analgesics according to their predominant symptoms and associated comorbidities (Hyams et al, 2016;Browne et al, 2018;Masuy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact pathogenesis of FD remains unclear, several pathophysiological mechanisms have been proposed to influence the etiology of FD, such as gastroduodenal motor dysfunction, visceral hypersensitivity, low-grade gastroduodenal inflammation, Helicobacter pylori infection, mental stress, and/or abnormal central nervous system processing through the gut-brain axis (Koppen et al, 2017;Walker et al, 2019;Shava et al, 2021). Most pediatricians commonly personalize the patient's medical treatment, including dietary modifications, prokinetics, antacids, antispasmodics, antidepressants, and analgesics according to their predominant symptoms and associated comorbidities (Hyams et al, 2016;Browne et al, 2018;Masuy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the decision to eradicate H. pylori should be individualized and preferred in patients with risk factors (i.e., peptic ulcer disease, gastric cancer, and Asian origin). A recent study in pediatrics found H. pylori to be present in 11% of the subjects with FD (n = 55) 36 .…”
Section: Altered Intestinal Permeabilitymentioning
confidence: 96%
“…Common stress examples in children include failing an exam, separating from a best friend, loss of a parent's job, and/or moving to a new place 17 . A recent study found that psychological stressors were the most common etiology for FD in children 36 . Abuse also predisposes to functional abdominal pain disorders, with one study showing that abdominal pain-predominant FGIDs were significantly higher in children who were abused sexually (34%), emotionally (25%), and physically (20%) when compared to those who were not abused 37 .…”
Section: Psychological Factorsmentioning
confidence: 99%
“…These findings support a previous study result, where the incidence of FD in children was between 3% and 27% ( 26 , 27 ). Altered visceral sensation, Helicobacter pylori infection, and gastrointestinal motor abnormalities have all been identified as major pathophysiological mechanisms for the development of FD ( 28 , 29 ).…”
Section: Disscusionmentioning
confidence: 99%